Optimisation of Tapioca Oxidative Reaction by Ozone Treatment: Effect of pH, Process Time and Temperature - Sumardiono, Siswo; Pudjihastuti, Isti; Supriyo, Edy; Siswanto, Anggun Puspitarini (Journal of Vocational Studies on Applied Research, 2020)
Modification of cassava starch was produced by oxidation using ozone treatment. The oxidized starch is used in the paper processing in the pulp and paper industries.  The aim of this research was to determine the effect of reaction conditions (pH and temperature) in produced oxidized starch. The oxidative reaction of cassava starch was using ozone as an oxidator while the operating condition was at temperatures of 30, 35, 40 and 45 oC in atmospheric pressure. The fixed variables were weight of cassava starch 80 grams, and volume of aquadest 200 ml. The change variables are reaction time (15, 30, 45 and 60 minutes) and pH solution (6, 7, 8 and 9). The product of oxidized starch was analyzed for carboxyl group according to JEFA method, swelling power according to Leach method and solubility according to Kainuma method. The result of this research shows with an increasing of pH reaction and reaction time, the carboxyl group and solubility increased, but swelling power decreased. The best condition was obtained at the pH of 9 with 60 minutes of reaction time.